Adopting Public Relations-Like Strategies to Promote Labour Feminism in Finland, 1965–1975 - Kurvinen Heidi (SAGE Publications Ltd, 2025)
When public relations as afield professionalized in Finland in the 1960s, it had knock-oneffects beyond the corporate world. As an example of this, I analyse various public rela-tions-like strategies adopted by a party political women’s organization, the FinnishWomen’s Democratic League. I show that as a radical left organization, the FinnishWomen’s Democratic League began to value media visibility in the mid-1960s, but italso continued to use more traditional communication forms, such as leaflets and work-place visits, to spread its ideological message. The changes of emphasis between variousforms of communication were affected by the politicization of Finnish society, whichcaused tensions between the bourgeois dominant public and the‘people’s democratic’counterpublic. My analysis is based on a close reading of minutes of Finnish Women’sDemocratic League meetings, press releases and other archival material, as well asPippuri, the organization’s internal magazine, andUusi  Nainen,a commercial women’smagazine published by the organization.